Ultra-fast high-temperature sintering (UHS) of Ce0.2Zr0.2Y0.2Gd0.2La0.2O2−δ fluorite-structured entropy-stabilized oxide (F-ESO). (June 2022) - Spiridigliozzi, Luca; Dell'Agli, Gianfranco; Esposito, Serena; Rivolo, Paola; Grasso, Salvatore; Sglavo, Vincenzo M.; Biesuz, Mattia
Abstract: Single-phase high entropy fluorite (Ce0.2 Zr0.2 Y0.2 Gd0.2 La0.2 O2−δ ) samples were synthesized by co-precipitation and consolidated by ultrafast high-temperature sintering (UHS) in less than 2 min. The chemical homogeneity of the sintered materials was confirmed by X-Ray Diffraction (XRD), Energy Dispersive X-ray Spectroscopy (EDXS), high-resolution EDXS using Transmission Electron Microscopy (TEM), and Raman spectroscopy. Compared to conventional sintering, UHS of high entropy ceramics was a hundred times faster and it resulted in highly dense microstructures (relative density > 93%) with nanometric grains. Ce0.2 Zr0.2 Y0.2 Gd0.2 La0.2 O2−δ densified under an UHS current of 20–25 A. An optimized step-wise UHS schedule was proposed to obtain dense, single-phase pellets with a reduced amount of defects. The extreme heating rates were found beneficial to limit grain coarsening and to obtain a single phase. Graphical abstract: Image, graphical abstract